Impact of yellow leaf virus on sugarcane commercial fields - Asinari, Florencia; Perez Gomez, Sergio Gregorio; Easdale, C.; Rago, Alejandro Mario; Balzarini, Monica; Cafrune, Eva Encarnacion (Springer, 2020)
A survey of Sugarcane yellow leaf virus (SCYLV) was conducted in northern Argentina in 2015 and 2016 using tissue blot immunoassay (TBIA). Results showed plant infection rates of 2.2–86.7% in sugarcane commercial fields from different growing areas. Percentage of infected leaves varied among cultivars and areas. NA 05–860 was the most infected cultivar (86.7% incidence). Virus genotypic diversity of SCYLV positive samples was analysed by reverse transcription polymerase chain reaction (RT-PCR). The virus genotype BRA-PER was found in all samples, followed by genotypes REU and CUB (36% and 8% of positive samples, respectively). The following co-infection patterns were found: BRA-PER + REU (34%); BRA-PER + CUB (6%); and the three genotypes, BRA-PER + REU + CUB (2%). Sugar content loss in cultivar LCP 85–384 infected with SCYLV was evaluated. Sugar yield reduction in SCYLV positive plants was statistically significant in dryland conditions (p < 0.0001). Our results indicate the high prevalence of SCYLV, the first detection of genotypes CUB and REU, and reduction in sucrose content related to SCYLV in Argentina. Disease management in the crop region should include the use of healthy planting material and SCYLV-tolerant cultivars.